Review of CCAFS Scaling Activities - Theissen, Arne H. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This review was commissioned by CCAFS Learning Platform for Partnerships and Capacity Building for Scaling Climate Smart Agriculture, with the aim to reflect on CCAFS project portfolio to highlight good practices and gaps in implementation of CCAFS Scaling Activities.